The impact of facemask on patients with COPD: A systematic review and meta-analysis - Chen, Xuwen; Zhang, Changqing; Ibrahim, Sani; Tao, Shunyu; Xia, Xiaoli; Li, Yi; Li, Caiyun; Yue, Feiyan; Wang, Xinhua; Bao, Shisan; Fan, Jingchun (Frontiers in Public Health, 2022)
Background: Since the emergence of COVID-19, mandatory facemask wearing has been implemented around the world to prevent viral transmission, however, the impact of wearing facemask on COPD patients were unclear. Methods: The current study undertakes a systematic review and meta-analysis of a comprehensive literature retrieval from 6 databases, based on the pre-determined eligibility criteria, irrespective of language. The risk of bias was assessed using an established instrument. We primarily focused on analysing ETCO2, SpO2, heart and respiratory rates, and also considered the impacts on physiological and exercise performance. A descriptive summary of the data and possible meta-analysis was performed. Forest plots were generated to pool estimates based on each of the study outcomes. Results: Of the 3751 publications considered, 6 publications were selected for a systematic review and 2 publications were included for meta-analysis, however, the quality of these 6 studies was relatively low overall. In the case of inactivity, the facemask wearing COPD cohort had higher respiratory rates than that of the non-facemask wearing cohort (MD = 1.00 and 95%CI 0.47 to 1.53, P < 0.05). There was no significant difference in ETCO2 (MD = 0.10 and 95%CI -1.57 to 1.78, P > 0.05) and heart rate (MD = 0.40 and 95%CI -3.59 to 4.39, P > 0.05) nor SpO2 (MD = -0.40 and 95%CI -0.84 to 0.04, P > 0.05) between the COPD patients with and without facemasks. Furthermore, it was observed that the only significant differences between the COPD patients with and without facemasks undertaking different activities were FEV1 (%) (MD = 3.84 and 95%CI 0.14 to 7.54, P < 0.05), FEV1/FVC (%) (MD = 3.25 and 95%CI 0.71 to 5.79, P < 0.05) and blood lactate (MD = -0.90 and 95%CI-1.73 to -0.07, P < 0.05). Conclusions: Wearing facemasks decreased the exercise performance of COPD patients, however had minimal impact on physiological indexes. Further investigations will be performed on the high-quality data from randomized control studies. Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=326265. Identifier: CRD42022326265 Keywords: Chronic obstructive pulmonary disease (COPD), facemasks, systematic review, meta-analysis